Three dimensional ink-jet printing of biomaterials using ionic liquids and co-solvents - Gunasekera, Deshani H.A.T.; Kuek, SzeLee; Hasanaj, Denis; He, Yinfeng; Tuck, Christopher; Croft, Anna K.; Wildman, Ricky D. (Royal Society of Chemistry, 2016)
1-Ethyl-3-methylimidazolium acetate ([C2C1Im][OAc]) and 1-butyl-3-methylimidazolium acetate ([C4C1Im][OAc]) have been used as solvents for the dissolution and ink-jet printing of cellulose from 1.0 to 4.8 wt%, mixed with the co-solvents 1-butanol and DMSO. 1-Butanol and DMSO were used as rheological modifiers to ensure consistent printing, with DMSO in the range of 41–47 wt% producing samples within the printable range of a DIMATIX print-head used (printability parameter < 10) at 55 °C, whilst maintaining cellulose solubility. Regeneration of cellulose from printed samples using water was demonstrated, with the resulting structural changes to the cellulose sample assessed by scanning electron microscopy (SEM) and white light interferometry (WLI). These results indicate the potential of biorenewable materials to be used in the 3D additive manufacture process to generate single-component and composite materials.